Anyone for Social Security Reform? - Partha Sen (Center for Economic Studies and ifo Institute (CESifo), 2016)
A reform of a pay-as-you-go social security makes the pensioners worse off and the working generations better off in the period of the reform (in a dynamically efficient economy without altruism). The observed reluctance across all age groups to support such reforms is usually explained by the insurance properties of these schemes. I propose an alternative in a two sector setting. Since the old consume labor-intensive goods like healthcare etc., the reform causes labor demand to fall and reduces wages. This effect could dominate the lower social security payments for the young. Thus both the young and old oppose the reform (that makes the unborn generations better off–the new steady welfare, with a higher capital stock, is higher).
Keywords: H55; 330; social security reform; two sector models; labor market